Estimation of D-dimer, C-reactive protein and ferritin in Covid-19 survivors in a North Indian Hospital, Lucknow, India. - Chetna Singla; Dhananjay Tiwari; Himali Jha; Mohammad Mustufa Khan; Sadaf Parveen; Roshan Alam (Acta Biochimica Indonesiana)
Background: Novel coronavirus disease (COVID-19), the disease caused by SARS-CoV-2, is a highly contagious disease. COVID-19 caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which was initially thought to affect only the upper respiratory tract, can affect almost all systems. COVID-19 survivors who are critically ill featured hyper inflammation and the associated biomarkers may be useful for risk stratification.